A new species of Alacran (Scorpiones: Typhlochactidae) from a cave in Oaxaca, Mexico - Francke, Oscar F. (Zootaxa, 2009)
Alacran chamuco sp. nov., a new eyeless, troglobitic scorpion from Te Cimutaa, Valle Nacional, is described. This is the second known species in the genus; sharing with Alacran tartarus a very similar trichobothrial pattern and the lack of “petite” trichobothria—both unique characters in the family Typhlochactidae. The new species differs from A. tartarus in the pedipalp finger dentition and the relative size of the telson. The two cave systems in Oaxaca where the two species of Alacran occur are approximately 75 kilometers apart.